ANALISIS KEBUTUHAN PENGEMBANGAN KOMPETENSI GURU DALAM MENULIS GUNA MENINGKATKAN MOTIVASI DAN KEBERHASILAN MENULIS BUKU - Ery Maritim (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2022)
This study aims to analyze the initial needs of developing the competence of elementary school teachers as an effort to increase motivation and success in writing books. The target of this study was a teacher at SD Hang Tuah Cluster, Pemalang District, Pemalang Regency. The method used in this research activity is descriptive qualitative with research instruments in the form of questionnaires and interviews. The use of data analysis techniques includes three stages, namely data reduction, data presentation, and drawing conclusions. Based on the analysis of the instrument, data was produced that the motivation and success of teachers in writing books is very low. The total number of teachers targeted for the study was 36 people. The percentage of teacher motivation in writing books is only 31% and success in writing books is at 3%. The low motivation and success of teachers in writing books is caused by internal conditions that are not conducive (limited knowledge about authorship) and inadequate facilities and infrastructure (time and capital). The results of this study are useful as an initial analysis of the need for teacher competency development in writing in order to have a strong motivation to start work so that teachers who are skilled in writing and productive in creating books as one of the published works.